The linkage between foreign direct investment, external debt and economic growth of South Africa (Journal of Academic Finance, 2025)
Purpose: A country's level of external debt and economic growth trends are regarded as imperative factors in attracting foreign direct investments of a country. Most developing countries are faced with high levels of external debt and lower growth. Due to such concerns, South Africa is among the developing countries that attract limited foreign direct investment. While investment is crucial for economic growth, hence an increase in foreign direct investment is beneficial for economic growth, especially in host economies. Thus, the study at hand examines the linkage between foreign direct investment, external debt, and economic growth of South Africa, using secondary time series data spanning from the periods of 1994 to 2021.Method: In attaining the study aim, the study employed the following econometric techniques, unit root tests, autoregressive distributed lag cointegration bound test, diagnostic tests, and stability tests.Results: The unit root results revealed that the variables are I(0) and I(1). The study distinguished a long-run link between foreign direct investment, external debt, and the economic growth of South Africa during the study period.Originality/relevance: The study contributes to existing literature on foreign direct investment, external debt and economic growth, and offers new recommendations from the South African context from 1994 to 2021. Hence, the analyzes in this study are important in guiding policies on foreign direct investment, external debt, and economic growth.
Keywords: South Africa; Foreign direct investment; External debt; Economic growth; Autoregressive distributed lag